A pharmacodynamic investigation to assess the synergism of orbifloxacin and propyl gallate against Escherichia coli - Abbas, Muhammad Aleem; Lee, Eon-Bee; Boby, Naila; Biruhanu, Biruk Tesfaye; Park, Seung-Chun (Frontiers in Pharmacology, 2022)
Escherichia coli (E. coli) infections are becoming increasingly difficult to treat, as antibiotic-resistant variants proliferate. Studies on novel methods to combat the spread of resistance and improve the performance of current antibiotics are vital. We aimed to boost the efficacy of the antibiotic orbifloxacin (ORB) against E. coli by combining it with a phenolic component, propyl gallate (PG). The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of ORB against the E. coli KVCC 1423 resistant strain were 128 μg/ml and 256 μg/ml, respectively. However, the MIC of ORB for the remaining E. coli strains was 0.5 μg/ml–2 μg/ml. For the combination of PG and ORB, the lowest fractional inhibitory concentration (FIC) index was less than 0.5, and the combination decreased the MIC of both drugs by 74%. The time-kill assay revealed the killing properties of both the drugs and the pharmacodynamic model (PD model) confirmed the strong killing properties of the combination as compared to the individual activities of the drugs. The ratio between MIC and mutant prevention concentration of ORB against E. coli 1400306 and 1,423 were 1:32 and 1:8, respectively. The combination of ORB and PG showed strong biofilm eradication and inhibited the motility of bacteria. The cell viability of the combination was > 80%. Therefore, we believe that ORB and PG in combination could be a possible antibacterial candidate that could minimize resistance and improve antibiotic potential.